El control interno y fortalecimiento de las capacidades en el programa nacional de infraestructura educativa, unidad de gestión educativa local Ucayali, Contamana 2023 - Sinacaisiva Marquez, Victor Raul (2024)
The main objective of this research was to determine the relationship between internal control and capacity building in the PRONIED, UGEL of Ucayali, Contamana 2023. The study was developed within an applied research framework, using a descriptive-correlational approach and a non-experimental design. The sample consisted of 195 Educational Institutions (EIs), to which a survey and a questionnaire were administered as instruments for data collection. The results revealed that internal control is perceived as regular by 27% of the participants, being attributed to the lack of an established code of ethics and the occasional lack of alignment of the organizational structure with the mission and strategic objectives. Regarding capacity building in the programme, 27% of principals consider it to be regular, especially due to the intermittent assessment of competencies developed during the teaching process. Finally, a significant relationship was identified between internal control and capacity building in the National Educational Infrastructure Program, UGEL Ucayali, Contamana in 2023, evidenced by a correlation coefficient of 0.800, indicating a strong and positive correlation between both variables. The significance of 0.000 confirms that this relationship is highly significant.